Can follicular fluid 8-oxo-2'-deoxyguanosine predict the clinical outcomes in ICSI cycle among couples with normospermia male? - Wassan Nori; Zeena Raad Helmi (Korean Society of Obstetrics and Gynecology, 2023)
Objective Oxidative stress (OS) occurs when excess free radicals damage the DNA. Moreover, 8-oxo-2'-deoxyguanosine (8-OHdG) is a well-known biomarker for OS linked to cellular damage and gene instability. However, its role in female subfertility has not been properly assessed. We aimed to examine the level of OS represented by 8-OHdG based on the cause of subfertility and to test its correlation with reproductive hormones, intracytoplasmic sperm injection (ICSI) parameters, and outcomes. Methods A cross-sectional study examined 108 subfertile couples with endometriosis, polycystic ovary syndrome (PCOS), tubal factors, and unexplained infertility undergoing ICSI treatment with two different stimulation programs. We included couples whose partners had normal sperm parameters. Levels of follicular fluid (FF) 8-OHdG were correlated with the causes of subfertility and fertilization rates and compared between pregnant and non-pregnant cases. Results Based on the causes of subfertility, FF 8-OHdG was the highest among endometriosis cases, followed by PCOS cases. Furthermore, FF 8-OHdG was higher in non-pregnant (2.37±0.75 ng/mL) vs. pregnant (1.58±0.39 ng/mL), P<0.001. A two-way analysis of variance showed that only subfertility affected ICSI outcomes, whereas the stimulation program did not. FF 8-OHdG correlated positively with female age and inversely with estradiol and good-quality embryos. The receiver operating characteristic estimated 8-OHdG cutoff value of 1.8 ng/mL predicted clinical pregnancies with 86.7% sensitivity and 74.4% specificity (P<0.001). Conclusion Higher FF 8-OHdG levels negatively impacted ICSI outcomes. FF 8-OHdG discriminated between cases of clinical pregnancy with good specificity and sensitivity. Because OS can be measured and treated, this opens up a therapeutic and prognostic avenue for improving ICSI outcomes.